Relational Narrative Inquiry Alongside a Young Métis Child and Her Family: Everyday Assessment Making, Pimatisiwin, Pimosayta, and Teacher Education and Development - Huber, Janice; Cardinal, Trudy; Murphy, M. Shaun (Frontiers in Education, 2022)
Understandings of diverse children, families, and communities/peoples as holding knowledge of and as practicing assessment is little recognized in research for, or in programs of, teacher education and development. Our paper shows the intergenerational relational living that Suzy, a young Métis child, experienced alongside her family as they imagined forward and remembered backward. This process shaped, and was shaped by, the family and Suzy’s continuous assessment of her ongoing making of a healthy life. We see important connections between Suzy’s and her family’s everyday assessment making practices and our experiences alongside Anishinaabe kwe scholar Mary Isabelle Young (Singing Turtle Woman), who lived with us Pimatisiwin (walking in a good way) and Pimosayta (learning to walk together). Dominant narratives of accountability in universities and schools most commonly serve the institution or government. Much potential opens in teacher education and development when we shift from these orientations to orientations that lift the particularities of each person and our collective responsibilities to all our relations. In this way we move closer to fulfilling our responsibilities to the people and worlds around us, to all of creation, the animals, plants, earth, and cosmos, and to the next generations.